(untitled) (Bangladesh Journal of Zoology, 2012)
The bacteriological quality of mola fish (Amblypharyngodon mola) from three local fish markets as fresh and as frozen from three departmental chain shops of Dhaka metropolis were analyzed. The microbial quality parameters varied with different sources and the quality was found to be poor for local market fish samples. In total 24 samples were considered for bacteriological quality analysis and 10 pathogenic isolates for antibiotic sensitivity test to 12 antibiotics. The total bacterial count ranged from 1.8 ± 0.25×104 to 6.5 ± 0.75 × 106 cfu/g for fresh and 5.5 ± 0.55 × 103 to 7.0 ± 0.80 × 105 cfu/g for frozen mola. The highest total coliform count of mola was 8.0 ± 0.55 × 104 and 6.1 ± 0.40 × 103 cfu/g for local market and departmental chain shop, respectively. All fresh and frozen samples were observed having high quantity of E. coli above 102 cfu/g. Furthermore, Salmonella-Shigella was identified in 67% samples (75% of fresh and 58% of frozen samples) varied from 0.9 ± 0.00 ×102 to 5.3 ± 0.30 × 103 cfu/g whereas Vibrio spp.was confirmed in 79% samples (83% of fresh and 75% of frozen samples) of which 90% samples exceeded 102 cfu/g. Similar pattern was observed in Staphylococcus spp. with 83% of fresh and 58% of frozen samples (63% of total samples) beyond 103 cfu/g. In case of antibiotic sensitivity pattern of the indicator and pathogenic isolates, all of them were resistant to amoxicillin and penicillin. Most of the isolates were sensitive to bacitracin, ciprofloxacin, erythromycin and streptomycin. The findings proved that mola fish under this study was more or less contaminated and local fish market samples were highly privileged with food borne pathogens which confirmed the unhygienic condition of the market as well as the presence of antibiotic resistance bacteria in mola fish may threat to public health safety. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12897 Bangladesh J. Zool. 40(1): 77-88, 2012